2017
DOI: 10.5539/jas.v9n9p168
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Impact of Conservation Agriculture on Smallholder Farmers’ Crop Productivity and Income in Luapula Province, Zambia

Abstract: Despite efforts to systemically disseminate Conservation Agriculture (CA) technology in Luapula Province of Zambia, the adoption rate remains limited. Furthermore, no empirical evidence has been presented on the factors influencing adoption of the technology or the extent to which farmers' livelihood has been influenced due to uptake of the technology. This study therefore examined the adoption and impact of CA on crop productivity and income on farming households in the Province. Using the 2012 Rural Agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…Hence it was positively correlated with adoption. The findings are in line with Manjunath [16] and inconsistent with Nkhoma [17]. Further, big farmers having large holdings with well economic conditions, better resource base and cropping intensity had more opportunities to try out new interventions which give them a better exposure and access to extension.…”
Section: Results In Thesupporting
confidence: 63%
“…Hence it was positively correlated with adoption. The findings are in line with Manjunath [16] and inconsistent with Nkhoma [17]. Further, big farmers having large holdings with well economic conditions, better resource base and cropping intensity had more opportunities to try out new interventions which give them a better exposure and access to extension.…”
Section: Results In Thesupporting
confidence: 63%
“…This finding was not unique to this study, several studies on CA in SSA (Arslan, McCarthy, and Lipper, 2013;Grabowski and Kerr, 2014;Kunzekweguta, Rich, and Lyne, 2017;Tambo and Mockshell, 2018) have reported that partial adoption of CA principles remain prevalent among smallholder farmers. When farmers were exposed to CA, they developed cropping systems (Nkhoma, Kalinda, and Kuntashula, 2017) that were intermediates between CA and CTP systems (Penot et al, 2015). These intermediate cropping systems were developed to address specific agricultural production constraints encountered by farmers under CA.…”
Section: Discussionmentioning
confidence: 99%
“…These intermediate cropping systems were developed to address specific agricultural production constraints encountered by farmers under CA. The partial adoption of CA was not only in terms of practices but also the proportion of cultivated land area under CA (Nkhoma, Kalinda, and Kuntashula, 2017). In this study, less than 50% of farmers reported practicing CA on the entire farm.…”
Section: Discussionmentioning
confidence: 99%
“…Na literatura internacional, dentre os estudos que objetivaram fazer mensurar o impacto da adoção das práticas conservacionistas em algumas variáveis de interesse, a exemplo do lucro e da produtividade, destacam-se Hammad & Borresen (2006), Uddin & Dhar (2016) e Nkhoma et al (2017). Baseados nos resultados desses trabalhos, constata-se que o impacto da adoção das práticas conservacionistas é incerto, podendo produzir rendimentos menores, equivalentes ou maiores do que o preparo convencional.…”
Section: Introductionunclassified